The Kingfisher illustrated animal encyclopedia - Burnie, David (Kingfisher LONDON, 2000)
An illustrated encyclopedia describing the physical characteristics, behaviour, and habitats of members of the following animal groups: simple animals, cnidarians, flatworms and roundworms, segmented worms, molluscs, arachnids, crustaceans, centipedes and millipedes, insects, echinoderms, chordates, catilaginous fish, bony fish, amphibians, reptiles, birds, and mammals